A review on bio-fuel production from microalgal biomass by using pyrolysis method. (February 2018) - Azizi, Kolsoom; Keshavarz Moraveji, Mostafa; Abedini Najafabadi, Hamed
Abstract: Due to the depletion of fossil fuels and their environmental issues, it is necessary to find energy resources which are renewable. Algal biomass becomes promising feedstock for bio-fuel production. They are considered as sustainable, renewable and effective biomass and bio-fuels obtained from them are more environment-friendly than fossil fuels. The aim of this work is to provide a state of the art review on pyrolysis of microalgae for generation of bio-fuels. Initially, some general aspects of biomass such as microalgae characteristics, different thermochemical processes and advantages of microalgae pyrolysis to produce bio-fuels are discussed. Then, different pyrolysis methods are explained and parameters affecting the process are addressed. Bio-fuels including gaseous, solid and liquid products have been characterized in a separate section. Finally, the technical challenges associated with microalgal pyrolysis commercialization are discussed in the last section of this article.